Evaluasi Tampilan Opac Di Perpustakan Pusat UIN Maulana Malik Ibrahim Malang - Mufid, Mufid (Pustakaloka, 2011)
The presence of OS (open sources) software causes Indonesiaâs higher education libraries strove to produce software. This Software provided modules, contained OPAC. The purposes of this research is to evaluate the performance of OPAC in Centre Library of Islamic State University (UIN) Maulana Malik Ibrahim Malang, using the standard of IFLA cheklist method. The result is that the OPAC performance of didnât fulfill the standard recommended by IFLA.